A method for faster application of process integration techniques in retrofit situations. (15th February 2021) - Bergamini, Riccardo; Nguyen, Tuong-Van; Bühler, Fabian; Bellemo, Lorenzo; Elmegaard, Brian
Abstract: Numerous process integration techniques were proved to be highly effective for identifying and estimating potential energy savings in the industry. However, they require high time and effort to collect and analyse process data. As a result, they do not constitute the common practice in the industry and opportunities for increasing the energy efficiency of industrial processes are missed. The paper presents a method, termed the " Energy-Saving Decomposition ", which is based on Process Integration techniques. It is intended for expeditiously outlining and promoting energy efficiency in the industry. Two screening tools, based on mathematical criteria and engineering experience, are employed for reducing the problem dimension before applying conventional design procedures. The first step disregards streams based on their contribution to the overall energy-saving potential, calculated utilising a novel energy-saving decomposition technique. The most promising network is then selected based on its energy-saving potential and size. The second step reduces the problem complexity further, employing economic considerations. This novel method was exemplified by application to a dairy factory: the outcomes and the method itself were compared to conventional Pinch Analysis techniques. The results showed that the developed method can simplify and reduce the time consumption of conventional Process Integration methods significantly, while identifying the most encouraging saving opportunities. The automatic algorithm allowed for reducing the problem size from 62 process streams of the existing plant to 22 streams requiring a computational time of only 135 s. The final retrofit design proposed was the same obtained with conventional Pinch Analysis, achieving a 23% reduction in the plant final energy consumption. Highlights: A novel expeditious method for process integration retrofit studies is presented. A novel decomposition of the energy-saving potential allows a reduction in problem size. A case study proves that the problem size is reduced from 62 to 22 streams with no loss in favourable design options. The method can be automated and is fast to compute, requiring a few minutes.